2014
DOI: 10.1179/2045772313y.0000000175
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation by surface electrical stimulation of peripheral nerves for reduction of detrusor overactivity in patients with spinal cord injury: A pilot study

Abstract: Objectives: To demonstrate reduction in detrusor overactivity using surface electrical stimulation of posterior tibial nerve (PTN) or dorsal penile nerve (DPN) in patients with spinal cord injury (SCI). Design: Patients with SCI with symptoms of urinary urgency/leaks, with cystometrogram (CMG) proven detrusor overactivity were recruited in this study. Ten persons with observable F-wave from tibial nerve were included in the PTN group. Five persons who had F-wave absent but preserved bulbocavernosus reflex were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A recent article reported that DGN stimulation acutely suppressed bladder contractions and increased bladder capacity in people with SCI, whereas tibial nerve stimulation, sacral nerve stimulation, and spinal stimulation did not improve (33). Ojha et al showed statistically significant improvement following TTNS and a trend of improvement following DGN stimulation (34). The DGN is a terminal branch of the pudendal nerve, a mixed sensory-motor nerve originating from S2 to S4.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 99%
“…A recent article reported that DGN stimulation acutely suppressed bladder contractions and increased bladder capacity in people with SCI, whereas tibial nerve stimulation, sacral nerve stimulation, and spinal stimulation did not improve (33). Ojha et al showed statistically significant improvement following TTNS and a trend of improvement following DGN stimulation (34). The DGN is a terminal branch of the pudendal nerve, a mixed sensory-motor nerve originating from S2 to S4.…”
Section: Findings In the Context Of Existing Evidencementioning
confidence: 99%
“…60 Electrical stimulation of the posterior tibial nerve or the sensory branch of the pudendal nerve is expected to improve urinary incontinence (LoE 3, GoR pending (not yet approved)). 61,62…”
Section: -2 Electrical and Magnetic Stimulation: Snm Might Bementioning
confidence: 99%
“…For example, sacral nerve stimulation (SNS) [4] therapy and transcutaneous tibial nerve stimulation (TTNS) [57] therapy have been used to treat subjects with SCI and NDO. Although both TTNS and SNS therapies have been reported to significantly improve urinary continence by increasing bladder capacity in subjects with incomplete SCI [57], a few recent studies report that TTNS and SNS did not produce a satisfactory outcome in related clinic trials [8, 9]. Moreover, these two neuromodulation approaches are not effective for increasing bladder capacity in individuals with complete SCI; it is still unclear why both approaches failed to improve urinary continence in these individuals.…”
Section: Introductionmentioning
confidence: 99%